Cultura de aprendizagem organizacional na indústria 4.0 : relações com engajamento no trabalho e intenção de turnover - Pereira, Giovana Urrutia (2020)
This study was conducted with the Career Development Study Group, which is the area of concentration in Social Psychology, the Graduate Program in Psychology, the School of Health and Life Sciences, the Pontifical Catholic University of Rio Grande The main objective was to investigate how the organizational learning culture relates to work engagement and turnover intent in Information Technology companies based in three Brazilian states (RS, PR and SP), considering the Industry 4.0. This is characterized by technological innovations that have been proposing the automation of both operational and intellectual processes, impacting the consumption and employment patterns, which are being created, modified and requiring adaptations by companies, government and individuals (Instituto de Estudos for Industrial Development [IEDI], 2017). In order to achieve the proposed objective, three studies were conducted: The first, methodological, was a qualitative research that aimed to propose the use of Cognitive Interview (CI) in the process of adaptation and validation of psychometric instruments in the Brazilian context. It had a sample of 10 participants who answered a pre-determined script interview using the “Verbal Polling” technique to explore individual perceptions about the Dimensions of the Learning Organization Questionnaire (DLOQ) instrument. It was concluded that the adoption of CI allowed to identify flaws in the item response process, making it possible to make changes in the wording and content, in order to reduce misconceptions and improve the instrument. The insertion of this step in the process proved to be important to qualify the adaptations and validations of instruments made for Brazil. The first study was an important part of the second study, which aimed to obtain evidence of validity and adequacy to the Brazilian context of the full version of the Dimensions of the Learning Organization Questionnaire (DLOQ) through its application in different organizations. A total of 188 professionals from five private companies located between the states of Rio Grande do Sul, Paraná and São Paulo participated in the study. They answered an online survey containing a sociodemographic and labor questionnaire to characterize the sample and the Dimensions of the Learning Organization Questionnaire (DLOQ). The data were submitted to confirmatory factor analysis, reliability tests and network analysis. Regarding the dimensionality of the DLOQ, the results indicated that the seven oblique factor theoretical model presented a better fit when compared to the one-factor model. In addition, all reliability indicators presented satisfactory values, higher than 0.87 (α) and 0.86 (Ω). Network analyzes indicated that correlations and associations between items within each dimension remained strong even after spurious correlations were eliminated, and pointed out which dimensions are most strongly related. Finally, the third study aimed to investigate whether there were relationships between the culture of organizational learning, engagement at work and the intention to turnover in Information Technology companies based in three Brazilian states (RS, PR and SP), considering the background Industry 4.0. The 188 study participants completed an online survey containing a sociodemographic and occupational questionnaire for characterization, the Dimensions of the Learning Organization Questionnaire (DLOQ), the reduced Utrecht Work Engagement Scale, and the EITBE Turnover and Job Search Intention Scale. Data were submitted to frequency, percentage, mean and standard deviation analyzes. The bivariate and partial correlations and the measures of proximity and expected influence were also analyzed. The results of the correlation and network analysis showed that organizational actions directed to the dimension connecting the organization with its environment have a direct effect on work engagement. The high rate of job engagement, in turn, has not been shown to reduce turnover intent. These results allow us to identify aspects of culture related to learning; which dimensions of culture relate directly to work engagement and their impacts on turnover intent. They also highlight elements of the organizational learning culture to be prioritized in interventions, in addition to offering indications on how to develop professionals within the organizational routine.